Pengembangan Usaha UMKM Hasrat Pada Masa Pandemi Covid-19 di Desa Dumati Kec.Telaga Biru Kab. Gorontalo - Abdullah, Abdullah; Malik, Taufik; Mohi, Safitri; Widyastari, Fitri (Madani: Jurnal Pengabdian Ilmiah, 2021)
This research is a research on the development of UMKM Hasrat businesses located in the village of Dumati, Kec. Telaga Biru. This research specifically aims at MSME business actors to increase their creativity to create new things into a big business so that they can create more jobs for people affected by the current Covid-19 pandemic. The method used in this research is a qualitative method that utilizes descriptive data in the form of written or spoken words from people and actors obtained from interviews and observations. Based on observations, the results obtained are that in addition to being a support for the community's economy, MSME Desire itself can also reduce poverty and unemployment rates with the most basic main problems faced by MSME actors, namely: 1.) Increased Raw Material Prices and 2.) Consumers who different characters. These are some of the problems that require more attention from the Gorontalo regional government, especially the cooperative and UMKM offices so that this business can grow and develop properly.